Situation Analysis of the Domestic Drug Materials Registration in Vietnam in the Period of 2009-2019 - Thi Hai Yen, Nguyen; Nhi, Nguyen Yen; Ngan, Thai Hue; Dat, Truong Van; Nghiem, Le Quan; Quan, Le Minh (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 37 No 1, 2021)
This study surveys the situation of domestic drug materials registration in Vietnam in the period of 2009-2019 based on the data retrieved from the Drug Administration of Vietnam’s website. The survey results show that during 2009-2019, there were 765 drug materials registeration numbers, of which domestic medicinal materials were among the most registered group with 196 types and 700 registration numbers; pharmaceutical ingredients ranked second with 45 registration numbers; adjuvants had 8 registration numbers, and the rest was capsules (12 numbers). This suggests that Vietnam tends to focus on medicinal materials and the increase in the registration numbers of this group is consistent with the development strategy of the Vietnamese pharmaceutical industry set by the Prime Minister. Yet, domestic drug materials including pharmaceutical ingredients, adjuvants and capsules have not really developed during the research period. Keywords Drug materials, medicinal materials, pharmaceutical ingredients, registration, Vietnam References [1] IMS Institute for Healthcare Informatics World Health Organization - Country office for India, FICCI (2012), Pharmerging shake-up, New imperatives in a redefined world", pp. 2-3. [2] Drug Administration, List of manufacturers of drugs and drug materials in Vietnam meeting GMP standards - updated to June 18, 2020. https://dav.gov.vn/danh-sach-cssx-thuoc-nguyen-lieu-lam-thuoc-tai-vn-dap-ung-tieu-chuan-gmp-cap-nhat-den-ngay-1862020-n2872.html, 2020 (accessed 8 August 2020) (in Vietnamese). [3] ACBS, The overview of Pharmaceutical Industry. https://www.acbs.com.vn/tin-tuc/n-a-3654-88, 2018 (accessed: 8 August 2020) (in Vietnamese). [4] The Prime minister, Decision of approving the master plan on medicinal plant development through 2020, with orientations toward 2030, No. 1976/QD-TTg, 2013 (in Vietnamese). [5] Ministry of Health, Decision on promulgating the list of 100 medicinal materials with high medical and economic value to focus on development in the period 2020-2030, 2019, (in Vietnamese). [6] Ministry of Health, Decision on promulgating the list of medicinal plants prioritized for development in the period 2015-2020, 2015 (in Vietnamese) [7] Vietnam Chamber of Commerce and Industry, EVFTA and Vietnam Pharmaceutical Industry pp. 5-6, 2017 (in Vietnamese). [8] The Government, Decree guidelines for implementation of the law on pharmacy, No. 54/2017/ND-CP, 2017 (in Vietnamese). [9] The Prime minister, Decision on approval the national key science and technology research program for developing the pharmaceutical industry to 2020, No. 61/2007/QD-TTg, 2007 (in Vietnamese). [10] The Prime minister, Decision on approving the planning for the development of the pharmaceutical industry to 2015, with orientations toward 2025, No. 81/2009/QD-TTg, 2009 (in Vietnamese).